Small and medium technology enterprises in Zhongguancun and Silicon Valley: Regional innovation system approach. Issue 1 (4th March 2019) - Trunina, Anna; Liu, Xielin; Chen, Jian
Abstract : Purpose: The purpose of this paper is to contribute to the understanding of similarities and differences between small and medium technology enterprises of Zhongguancun in China and Silicon Valley in the USA in the following aspects of their activities: scale, diversity and the strength of entrepreneurial networks; quality of collaboration network; reputation in the sense of stakeholders' perception at the local market; and foreign networks. Design/methodology/approach: The study uses a survey method. The analysis of variance statistical technique was applied to each aspect. Findings: The investigation reveals that Chinese companies have more stakeholders among relatives and friends, government, universities, accounting/law, as well as collaborate more with competitors and suppliers, while the US companies have more and collaborate diverse relations with its clients. In America, companies tend to trust their partners more than they do in China. For Chinese companies, the local government appraises business more than the USA. Employees from the US companies also take more pride in telling others that they are members of the business. Domestic customers positively rate business products. Chinese companies actually have better access to foreign resources than the USA and collaborate more with their foreign stakeholders. Practical implications: Understanding the distinctive features of each regional system is crucial for the success of small and medium technology enterprises for both Chinese and US entrepreneurs. Originality/value: This paper is a pioneer in the comparison and analysis of the two regions.